2022
DOI: 10.1039/d2ob01187e
|View full text |Cite
|
Sign up to set email alerts
|

Organic acid catalysed Minisci-type arylation of heterocycles with aryl acyl peroxides

Abstract: A metal-free method for the Minisci-type arylation of heterocycles with aryl acyl peroxides has been reported. This strategy enables the rapid and simple synthesis of a series of Minisci-type adducts...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…For example, Li and coworkers 409 have recently reported that the mild thermal treatment of dibenzoyl peroxide (Ph− COO) 2 generates Ph−COO • radicals that lead to Ph • radicals after decarboxylation. The latter can then attack phen in position 2, leading to 202 (Scheme 68).…”
Section: Activation Of C 2 By Coordination Of Metal Ionsmentioning
confidence: 99%
“…For example, Li and coworkers 409 have recently reported that the mild thermal treatment of dibenzoyl peroxide (Ph− COO) 2 generates Ph−COO • radicals that lead to Ph • radicals after decarboxylation. The latter can then attack phen in position 2, leading to 202 (Scheme 68).…”
Section: Activation Of C 2 By Coordination Of Metal Ionsmentioning
confidence: 99%